Resting Behavior of Blood-Fed Females and Host Feeding Preferences of Aedes aegypti (Diptera: Culicidae) Morphological Forms in Senegal. Issue 6 (24th June 2021) - Diouf, Babacar; Sene, Ndeye Marie; Ndiaye, El Hadj; Gaye, Alioune; Ngom, El Hadj Malick; Gueye, Assiyatou; Seck, Fatoumata; Diagne, Cheikh Tidiane; Dia, Ibrahima; Diallo, Mawlouth; Diallo, Diawo
Abstract: Aedes aegypti (Linnaeus) is the main vector of most arboviruses in tropical and subtropical urban areas. In West Africa, particularly in Senegal, domestic and wild populations have been described. Both Ae. aegypti aegypti ( Aaa ) and Ae. aegypti formosus (Aaf ) were found in progenies of Ae. aegypti families from several localities of Senegal. However, nothing is known about their resting and trophic behavior, which are key data for vector control. To fill this gap, blood-fed mosquitoes were collected monthly indoors and outdoors with BackPack aspirators and BG-Sentinel 2 traps between July and November 2019 from four urban sites. The enzyme-linked immunosorbent assay technique was used to analyze blood-fed Aaa and Aaf specimens. Both forms were found resting in all investigated places with the highest proportions found in scrap metals (51.7% for Aaa and 44.1% for Aaf ) and used tires (19.2% for Aaa and 26.1% for Aaf ). Blood-fed Aaf females showed lower occupation of the indoors environment compared to Aaa . Overall, the percentages of single bloodmeals from human were 80.5% (916/1138) for Aaa and 71.1% (263/370) for Aaf . A low frequency of other domestic hosts, including bovine, ovine, and cat were detected for both forms. This study provides the first data on resting and trophic behavior of Aaa and Aaf in Senegal. Both forms showed differences in their resting behavior but fed primarily on human and highlight the risk of arboviruses transmission in urban areas.